The art of insight : how great visualization designers think - Cairo, Alberto, 1974- (Hoboken, New Jersey : Wiley, 2024)
"The Art of Insight: How Great Visualization Designers Think is a book about making design decisions in difficult situations. Decision-making is an essential skill for designers because anyone can create a data visualization with just a few clicks. Data is easily available online, and multiple free and easy-to-use software tools have appeared in the past few years. These developments have led to an explosion in the amount and variety of graphs, charts, and maps. We see them everywhere, from news publications to social media. Cairo explains this is a positive phenomenon, but only if the creators of those visualizations are able to think clearly and ethically about what they are doing. As the famous line from the 2002 Spider-Man movie says, with great power comes great responsibility. Visualization books often focus on rules for creating charts and maps, but rarely explain the origin of those rules. Readers are told to start all graphs at a zero baseline, never use pie charts, maximize the data-ink ratio, and so on. Cairo argues that this approach is misguided: it shoehorns designers into a single rigid mode of thinking, based only on the perspective of the book's author or authors"--
Includes bibliographical references.
Keywords: Design -- Methodology; Visualization